MODEL PENDIDIKAN KARAKTER SEPENUH HATI PADA SISWA MADRASAH IBTIDAIYAH - Muhammad Fahmi Hidayatullah (Universitas Islam Malang, 2019)
AbstrakIt is very important for schools that educate children by making educational innovations to maximize the inculcation of character in them. This is inseparable from the challenges of technological development and globalization which easily influences children to commit social deviations. Wholehearted education as an alternative solution for dedication to elementary school children. Learn from madrasas ibtidaiyah how to instill the value of character in order to form a strong and steadfast person with his principles through a wholehearted educational process. Keywords: Education Model, Wholehearted, Islamic elementaris scholl